The role of governments in promoting the transition to a knowledge economy and the challenges they face - Alsubhi, Wafiah Othma; Alyahyan, Maha Saleh Saad (Journal of Educational and Psychological Sciences, 2025)
This research explores the role of governments in promoting the transition to a knowledge economy, focusing on the policies and strategies adopted by countries-particularly the Kingdom of Saudi Arabia to achieve this shift amid global challenges. The study aims to analyze the governmental mechanisms that support knowledge-based transformation and to identify the key success factors and barriers to implementation. The researchers employed a descriptive-analytical methodology to examine governmental efforts and policies, incorporating both local and international experiences. The findings revealed that the success of transitioning to a knowledge economy largely depends on the existence of an advanced digital infrastructure, an education system centered on skills and knowledge, a supportive environment for innovation, and effective funding for research and development. The study recommends enhancing partnerships between the public and private sectors, providing financial incentives for innovation, aligning education with market needs, and creating a flexible legislative environment that enables the growth of entrepreneurship and the digital economy.